Tamil nāṭaka varalāṟṟil Pāratitācaṉ - Vīrācāmi, Tā. Vē. (Tārāpuram Vēṅkaṭācala), 1931- (Manimekalai veliyeedu ; Viṟpaṉai urimai, Tamiḻp Puttakālayam, 1981)
Study of the contribution of Pāratitācaṉ, 1891-1964, Tamil litterateur to the development of Tamil drama; transcript of the 1980 Swami Sankaradas Endowment lecture, Madurai Kamaraj University.